Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Effects of exogenous application of Ursolic acid on apple cuticular wax biosynthesis and postharvest quality preservation - Wei-Teng You; Zi-Heng Wang; Zhi-Chao Meng; Kui-Tao Zhang; Qi Zhang; Xu Han; Hang Zhang; Xiao-Min Xue; Shang Wu; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Postharvest Biology and Technology, 2026)

Responses of biogeochemical cycles to polyethylene microplastics exposure during aerobic fermentation of dairy manure - Qianting Zhuo; Ranran Wei; Ya Su; Haochen Shao; Lujia Han; Guangqun Huang (Bioresource Technology, 2026)

Beyond direct pathway engineering: reprogramming Fusarium fujikuroi from a GA3 producer into a GA4+7 factory - Hang Xiao; Tao-Xu Lu; Ming-Han Li; Ya-Ling Yi; Hao-Yang Li; Yu-Ke Cen; Zhi-Qiang Liu; Yug-Guo Zheng (Bioresource Technology, 2026)

Screening optimum reference genes for quantitative real-time polymerase chain reaction analysis in invasive apple snail, Pomacea canaliculata under different conditions - Ya-Wen Chang; Han-Di Long; Ran Wei; Zhen-Jun Sun; Guo-Xian Zha; Cheng-Dong Wu; Hong-Fang Xie; Jie Hu; Yu-Zhou Du (Molecular Biology Reports, 2026)

A novel control strategy: Suppressing histone acetyltransferase ClHAC703 with curcumin to prevent germination of the invasive weed Cenchrus longispinus - Xiao-Min Han; Jia-Ying Wang; Yan-Ping Fu; Bin Guo; Wei He; Ya-Hui Wei (Plant Science, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Low-temperature storage alleviates internal browning in harvested pineapple fruit by inhibiting AcWRKY75-mediated activation of phenylpropanoid pathway genes - Ming-zhe Yang; Ya-han Tan; Shan Jiang; Ying-ying Tan; Wei Wei; Ke-qian Hong; Jian-ye Chen (Postharvest Biology and Technology, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Cucurbit[7]uril as an alternative macrocycle for steroid hormone removal by composite nanofiber membranes - Han-Ya Lin; Babak Minofar; Zdenek Futera; Andrea I. Schäfer (Chemical Engineering Journal, 2026)

A capture-kill-remove Nanoplatform with synergistic Photothermal/enzyme-like activity for complete bacterial eradication and lysate removal - Linyan Tang; Qiuting Duan; Qian Zhang; Ying Han; Ya Xu; Dezhi Yang (Chemical Engineering Journal, 2026)

Outdoor thermal comfort differences among orthopedic, oncological and chronic-disease patients in cold-region hospital spaces - Ya Tuo; Songtao Cui; Minghui Sun; Weijie Xia; Songjiang Han; Meng Zhen; Ming Zhang; Kai Nan (Building and Environment, 2026)

Removal efficiency and mechanisms of natural mineral materials for bacteriophages MS2 and ΦX174 in aqueous environments - Ying Song; Ya-ting Wang; Ying Han; Rong-xuan Xu; Yang Wang; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Multimodal deep fusion of Low-Field NMR and proton Density-Weighted imaging for interpretable detection of Saline-Alkali stress in wheat - Ying Gu; Guoqing Feng; Ya’nan Zhou; Han Zhang; Cheng Wang; Liping Chen; Bin Luo (Computers and Electronics in Agriculture, 2026)

Fluorescence and SERS dual-mode sandwich lateral flow test strip utilizing concanavalin A modified trimetallic polydopamine with rhodamine B loaded UiO-66 immunoprobe for visual and sensitive detection of Escherichia coli - Wen-Bo Zhao; Xiao Liang; Zi-Tao Zhong; Liu Yuan; Ji-Tao Li; Qiu-Lan Li; Qin-Qin Han; Ya-Ling Yang (Food Bioscience, 2026)

Water-resistant electroluminescent devices with temperature tolerance and mechanical cyclic stability based on hydrophobic nanocellulose - Fang Deng; Ya Lu; Haoyu Sun; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2026)

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Physiological, transcriptomic, and metabolomic insights into the sugar stress tolerance mechanisms of Clavispora lusitaniae and its fermentation potential - Ya Zhang; Siyi Liu; Runshen Zhao; Fanghang Qiu; Meiyue Han; Qiumei Zhang; Xingquan Han; Xucheng Zhu; Akhtiar Ali; Weiwei Li; Xiuting Li; Baoguo Sun (International Journal of Food Microbiology, 2026)

Corrigendum to “Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef” [Food Res. Int. 236 (2026) 119292] - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Unveiling the enigma of anxiety disorders and depression: from pathogenesis to treatment - Han-Qing Pan; Tian Xia; Yu-Ya-Nan Zhang; Hui-Jie Zhang; Meng-Jie Xu; Jing Guo; Yan Liu; Xue-Ying Bai; Qian Liu; Wei-Zhu Liu; Wen-Hua Zhang; Qi-Gang Zhou; et al. (Science China Life Sciences, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Unraveling the molecular evolution and immune functions of Lr-CD40 in Lethenteron reissneri - Liang Zhao; Zihao Yan; Mingwei Du; Xiaoping Song; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Feng Sun; Yinglun Han (Fish Physiology and Biochemistry, 2026)

Enhancing unconfined compressive strength of granite residual soil through synergistic application of microorganisms and jute fibers - Jiaxin Kang; Wenjing Liang; Hao Peng; Ya Wang; Fang Dang; Yunru Zhang; Hong Guo; Han Bao (Bulletin of Engineering Geology and the Environment, 2026)

Engineering-grade monitoring of floating-roof oil tanks using amplitude-only TerraSAR-X imagery and dual geometric pipelines - Yi-Keng Chen; Zheng-Shun Su; Ya-Lun S. Tsai; Su-Wei Chang; Jen-Yu Han; Chun-Jia Huang (International Journal of Remote Sensing, 2026)

Neuro-symbolic framework for multi-USV coordination: COLREGs-compliant and energy-efficient smart navigation - Shuai Huang; Yi-Feng Chen; Mao-Yuan Sun; Jia-Ning Gao; Yu-Han Zhou; Jing-Wen Zeng; Cheng-Chen Wang; Ya-Ze Han; Yang Xiong (Frontiers in Marine Science, 2026)
Introduction Coordinating multiple unmanned surface vehicles (USVs) in coastal waters requires simultaneous consideration of COLREGs compliance, real-time response, energy efficiency, fault tolerance, and semantic scene understanding. Existing approaches typically address only part of this problem and provide limited support for integrated fleet-level coordination. Methods This paper proposes NSC-Marine, a neuro-symbolic framework that conceptually addresses these coupled constraints. It combines multimodal causal perception, LLM-based rule reasoning, energy-aware motion planning, and distributed fault reconfiguration within a dual-rate control architecture. To improve deployment safety, semantic reasoning is used to generate structured constraints, while low-level motion execution remains under deterministic planning and control. Results The framework is evaluated strictly within a physics-based simulation environment with approximately 70% overall fidelity, involving 1,000 trials of 20–100 USVs under Beaufort Scale 3–5 conditions. Under these simulated conditions, NSC-Marine achieves 88.7% ± 2.3% COLREGs compliance, 82.3% mission success under compound faults, and 13.6% energy reduction relative to the RLCA baseline, while maintaining a 320 ms critical-path latency. Discussion These metrics reflect an idealized simulation baseline and must not be generalized to physical deployment readiness. Real-world performance remains unvalidated, and staged hardware-in-the-loop testing and field trials are required to characterize the system’s actual behavior under physical disturbances.

Extraction and identification of polyphenols from Viburnum fordiae fruits with their α -amylase and α -glucosidase inhibitory activities - Jia Chen; Wei Ji; Hong-Juan Zhou; Zi-Han Wang; Meng-Ya Yang; Jian-Hua Shao; Chun-Chao Zhao (Natural Product Research, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Target-oriented molecularly imprinted polymers enable rapid ambient ionization mass spectrometric analysis of trace tetrachlorobisphenol a in environmental samples - Ya Jiao; Shuo Gao; Xiaoxuan Han; Yong Tian; Xiaoxu Huo; Jianwei Zhao; Xiaofeng Dong; Chunguang Liu; Weiliang Wang; Guifen Zhu; Xuwei Chen; Ming-Li Chen (Journal of Hazardous Materials, 2026)

Climate and anthropogenic drivers of spatiotemporal variation in ecosystem regulation service value across China (2000-2023) - Nitu Wu; Sier Ha; Guodong Han; Haiwen Wang; Ya Na (Journal of Cleaner Production, 2026)

Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

Aggregated-state remodeling of quinoa protein gels by thermal pretreatment and transglutaminase - Zhen-Yang Quan; Ting-Ting Ji; Jia-Han Liu; Dong-Ping Zeng; Xiu-Nan Zhang; Ying Chen; Jian-Ya Qian; Liang Zhang (Food Chemistry, 2026)

A review of the environmental distribution, sources, transformation, and (eco)toxicities of tetrabromobisphenol A, its derivatives, and by-products - Yanfeng Zhang; Weihao Xu; Ya Jiao; Xiaoxuan Han; Chenshi Luo; Yong Tian (Environmental Monitoring and Assessment, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

An integrated geochemical and isotopic framework for nitrate source apportionment in a shallow coastal aquifer under multiple environmental pressures - Sa Xiao; Ya Wang; Tao Gu; Xiaoli Yang; Ting Han; Chaoan Mai (Water Research, 2026)

Development of a MALDI-TOF nucleic acid mass spectrometry-based assay for the detection of 10 major avian diseases - Ya Zhao; Yunlei Chen; Xiao Han; Pengli Kong; Shiqi Song; Hui Qiu; Zihong Ye; Xiaofeng Zhang; Jiangbing Shuai (The Veterinary Journal, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Identification of AcbHLH82 involved in internal browning of pineapple fruit by reducing ROS accumulation via activation of ROS scavenging genes - Ming-zhe Yang; Ya-han Tan; Ying-ying Tan; Wei Wei; Ke-qian Hong; Jian-ye Chen (Postharvest Biology and Technology, 2026)

Contact toxicity and transcriptomic responses of Tribolium castaneum to Trichosanthes kirilowii stem extract - Shanshan Gao; Haofei Ya; Han Zhang; Guangyan Zhang; Zhiyu Zhu; Menyi Guo; Shuang Xue; Kunpeng Zhang (Journal of Asia-Pacific Entomology, 2026)

Clinical efficacy of Fufang Zaofan Pills and their immunomodulatory effects on peripheral blood dendritic cells in individuals with lower-risk myelodysplastic syndrome - Fei-Fei Zhang; Xiao-Yun Gao; Li-Lai Jiang; Xiu-Wen Yu; Shu-Zhen Yu; Ya-Jun Jiang; Xiu-Hua Han (Journal of Molecular Histology, 2026)

Substantial underestimated quantities of analytes following analyte filtration - Jie Han; Huachen Ma; Longkai Qiao; Aiqin Wang; Shuangshuang Wei; Yilong Ren; Ya Liu; Eric Lichtfouse (Environmental Chemistry Letters, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Thickness variation of black soil on sloping farmland in northeast China from 1963 to 2023 - Chang Liu; Gang Liu; Chenxi Dan; Enshuai Shen; Ya Liu; Qiong Zhang; Han Luo; Chutian Zhang; Zhen Guo; Kaishan Song (Soil and Tillage Research, 2026)

Text mining and machine learning based health risk prediction for soil polycyclic aromatic hydrocarbons at typical coal-fired industrial sites in china - Lu Han; Hanyuan Gu; Mengfang Chen; Zhanfei He; Yufei Jia; Yudong Feng; Jing Li; Ya Zhu; Ye zou (Journal of Hazardous Materials, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

Polysaccharide-based inflammatory microenvironment-responsive nanocarriers for ulcerative colitis: Advances in design, mechanisms, and therapeutic applications - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2026)

Fast fluidization of dry acid pretreated wheat straw and consequent continuous bioconversions for l-lactic acid production - Tao Han; Ya Wang; Bin Zhang; Jie Bao (Bioresource Technology, 2026)

Systematic metabolic engineering of Corynebacterium glutamicum for enhancing L-isoleucine production - Zhi-Han Gong; Ya-Ru Zhang; Jian-Zhong Xu (Systems Microbiology and Biomanufacturing, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

A Moon image point spread function deconvolution framework for satellite Earth observation image restoration - Han Lin; Ya Su; Binglong Chen; Qunyong Wu; Zhiqing Zhang (International Journal of Remote Sensing, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Binding of fruit and vegetable cell wall materials to dietary cholesterol in the gastrointestinal fluid reduces cholesterol bioaccessibility: mass transfer mechanism and metabolic benefits - Yan-Ming Sun; Sivakumar Manickam; Erico Marlon Moraes Flores; Ya-Ning Shi; Yue Wu; Yong-Bin Han; Yang Tao (Food Bioscience, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

Optimized Up-Down Deconvolution for Source-Side Ghost Wave Suppression in Multi-Component Ocean-Bottom Seismic Data - Xiangchun Wang; Qingxian Zhao; Zhendong Liu; Meifeng Han; Ya Zhou (Journal of Ocean University of China, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Sub-denaturing thermal pretreatment modulates lactoferrin-quercetin interactions: Structural dynamics, binding mechanisms, and functional synergy - Si-Jie Wu; Qi-Bin Kuang; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Hydrocolloids, 2026)

AID/APOBEC-like cytidine deaminases are important mediators of VLR-based adaptive immunity in lampreys - Zihao Yan; Jingjing Lu; Yuesi Zhou; Liang Zhao; Ding Li; Huining Jia; Ayqeqan Nurmamat; Min Xiu; Shuyuan Zhang; Ruyu Zhuang; Ya Pang; Tiesong Li; et al. (Fish & Shellfish Immunology, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

From strong to switchable adhesion: Gecko-inspired design strategies and practical applications - Changlin Shen; Weimin Heng; Chunxiao Wu; Xinrui Hou; Yichen Fan; Ya Li; Yekun Han; Qi’ao Yang; Lei Wang; Zhilong Peng; Shaohua Chen (Chemical Engineering Journal, 2026)

Phycocyanin-loaded W1/O/W2 double emulsion-filled sodium alginate gel beads reinforced by chitosan for enhanced stability and sustained release performance - Miaomiao Han; Ya Zhao; Jiao Yu; Mohammad Molaveisi; Qilong Shi (Algal Research, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

A tailored multi-agent reinforcement learning based approach for enhancing collaborative twin ocean-going ships energy efficiency - Peixiu Han; Yixuan Wang; Zhongbo Liu; Ya Zhong; Chunxin Yan (Ocean Engineering, 2026)

Volumetric landscape: The mix characteristics and co-agglomeration of 3D space use in compact cities - Yi-Ya Hsu; Hoon Han (Landscape and Urban Planning, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Spatiotemporal dynamics of riverine microbial community structure and microbial interaction with changes of dissolved organic matter in Liaohe River Basin - Tao Ya; Weize Li; Xiaohan Yan; Lu Han (Journal of Environmental Chemical Engineering, 2026)

Algae penetration and taste and odor compounds production in drinking water treatment plants: seasonal variations and risk assessment - Ya Cheng; Caiyun Ma; Gang Wen; Chaoyang Zheng; Wenle Tian; Kailin Sha; Xinru Han; Tinglin Huang (Journal of Environmental Sciences, 2026)

Cloning, tissue distribution, and stimulus-responsive mRNA expression of CD10 (neprilysin) in Lethenteron reissneri - Liang Zhao; Zihao Yan; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2026)

Design and synthesis of multifunctional polyaspartic acid derivatives as green water treatment agents: Calcium scale inhibition, antibacterial activity, and fluorescence properties - Ying Zhang; Lin-Lin Zhao; Yu Han; Yu-Xia Wang; Zhong-Yan Cao; Ya-Min Cheng; Ying Xu (Desalination, 2026)

Phytochemical characterization and multi-target mechanism of Gleditsia sinensis Fructus in lung adenocarcinoma treatment - Zhengyuan Fan; Di Han; Tingting Shen; Ya Li; Suxiao Liu; Suyun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Isolation and antibacterial activity of three new flavonol compounds from Sophora flavescens - Si-Han Wang; Xiang-Yu Zhao; Zhi-Kang Chen; Yun Gao; Xin-Min Li; Ya-Juan Gao; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

Comparison of apple fruit waxes and quality when stored at 25 ℃ under different humidity conditions - Kui-Tao Zhang; Min-Min Zhou; Wen-Shuo Xue; Zi-Heng Wang; Wen-Teng You; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Postharvest Biology and Technology, 2026)

Synergistic microbial co-culture of Saccharomyces cerevisiae and Clostridium kluyveri enhances ethyl hexanoate production for stable flavor synthesis in strong-flavor Baijiu - Qiumei Zhang; Ru Zhang; Xi Chen; Meiyue Han; Ya Zhang; Weiwei Li; Xiuting Li; Jianxiong Hao; Baoguo Sun (Food Bioscience, 2026)

Programmable and multi-stimuli responsive hydrogel actuator mediated by nanocellulose with intrinsic self-sensing capacity - Ya Lu; Shengnan Li; Fang Deng; Yiying Yue; Shuijian He; Shaohua Jiang; Mingqiang Ye; Yihui Zhou; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2026)

Microbial-electrochemical driven simultaneous biogas upgrading and high-value medium-chain carboxylic acid production - Ya-Ru Wang; Chuan Chen; Shu-Tong Wu; Zi-Han Wang; Lei Zhao; Juan Tong; Kai-Kai Wu; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren (Bioresource Technology, 2026)

Mechanisms and Therapeutic Potential of Targeting Mitophagy in Neurodegenerative Diseases - Ya-Ning Wang; Xing Wang; Qin Huang; Yun Yang; Tao Wang; Xin-Hui Qu; Xiao-Jian Han (Molecular Neurobiology, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Presence of Astrocytic S1R/5-HT1A Heterocomplex in the mPFC: A Putative Link to S1R Activation Mediated Faster Antidepressant-Like Effects - Peng Ren; Jing-Ya Wang; Meng-Jie Xu; Han Ni; Shuang Zhang; Chen-Xing Yue; De-Yi Yang; Yun-Feng Li (Molecular Neurobiology, 2026)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Recombinant GnRH6-kisspeptin-CRM197 vaccine inhibits reproductive function in male rats and dogs - Yanyun Zhu; Mengxian Li; Xiangyang Jiang; Dongyuan Fu; Zhihao Pan; Zhuoya Wu; Kejian Han; Ya Liu; Yunsheng Li; Tong Yu; Kaiyuan Ji; Mengling Peng; et al. (The Veterinary Journal, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Evaluation of resistivity attenuation models in geotechnical media with penetration depth - Zhijie Li; Ya Chu; Guojun Cai; Chao Yan; Songyu Liu; Aimin Han (Journal of Applied Geophysics, 2025)

Exploring the regulation mechanism of digestibility of starch-polyphenol-protein ternary system by pH from multiple perspectives - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Assembling L-malic acid and Co-MOF in ultrasonically synthesized pectin/gelatin films: A versatile food preservation composite film - Xu Han; Wen-Shuo Xue; Shang Wu; Qi Zhang; Wei-Teng You; Zi-heng Wang; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Food Chemistry, 2025)

Removal of starch granule-associated lipids from normal and waxy wheat starches: Effects on properties, retrogradation, digestion, and molecular mechanisms - Han Tao; Hai-Yuan Zhou; Shan Li; Ya-Ni Li; Wan-Hao Cai; Hui-Li Wang (Food Chemistry, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Innovative analytical techniques for identifying metabolites of the UV filter homosalate through UPLC–MS: Environmental and health implications - Yi-Shiou Chiou; Chia-Hui Liu; Zih-Han Wu; Min-Feng Tseng; Shih-Chin Chang; Ya-Wen Chang; Chueh-Yi Huang; Chia-Lung Shih (Environmental Pollution, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Polarization-sensitive optoelectronic synapse with all-optical modulation enabling static image processing and microscopic biological motion detection - Kaiqi Shi; Jiaqi Han; Ya Lin; Ye Tao; Yongxing Zhu; Xuanyu Shan; Xiaoning Zhao; Hui Su; Zhongqiang Wang (Chemical Engineering Journal, 2025)

Steroid hormone micropollutant removal from membrane bioreactor effluents using single-walled carbon nanotube composite nanofiber membranes - Han-Ya Lin; Minh N. Nguyen; Andrea I. Schäfer (Chemical Engineering Journal, 2025)

Nanogel cage based on oxidized sodium alginate sacrificial template: Enhanced stability and protein crosslinking performance of immobilized TGase - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao Zhang (Carbohydrate Polymers, 2025)

Public Perception and Conservation Behavior of Urban Wetland Ecosystem Services: a Study Based on Family Life Cycle Perspective - Huiqing Han; Ya Huang; Yuanju Jian (Wetlands, 2025)

Exploring the evolutionary conservation and functional implications of Endothelin Converting Enzyme 1 (ECE1) in lamprey (Lethenteron reissneri) - Shuyuan Zhang; Zihao Yan; Ayqeqan Nurmamat; Ruyu Zhuang; Yuesi Zhou; Min Xiu; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2025)

Piezopolymers to transform motion into electrical energy for chemical-free disinfection - Chaoqi Wang; Weilong Kong; Ya Liu; Eric Lichtfouse; Jie Han (Environmental Chemistry Letters, 2025)

Two-Dimensional Joint Inversion of Direct Current Resistivity and Seismic Refraction Travel-Time Data Constrained by Gaussian Mixture Clustering - Li-hui Wang; Miao Peng; Han-dong Tan; Shu-ya Wang (Applied Geophysics, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Corrigendum to “the different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies” [toxicology and applied pharmacology volume 503, October 2025, 117505] - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Research progress on genes and regulatory mechanisms of drought resistance in rice - Nuo Gong; Yingchun Han; Ziwen Wang; Ya Wang; Yanxiu Du; Zhen Chen; Hongzheng Sun; Junzhou Li (Plant Science, 2025)

Comprehensive insights into the effect of color, texture, flavor and microbial community driven via yak bone-derived collagen peptides combined with tea polyphenols as a versatile additive in fermented sausages - Zhaoyang Song; Ya Zheng; Yabin Ma; Wenjing Ni; Yinjuan Cao; Ling Han; Qunli Yu (Food Research International, 2025)

New insights into the regulation mechanism of starch digestibility by polyphenol structures in starch-polyphenol-protein ternary system - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Evolutionary conservation and Immunoregulatory function of LOXL3 gene in lamprey - Ya Pang; Zihao Yan; Yicheng Gao; Ding Li; Liang Zhao; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2025)

Long-term no-tillage practice with re-used plastic film mulching exacerbates bacterial ecological risks in dryland–based on plastisphere - Ya-nan Han; Yang Yi; Jian-yu Su; Chao Fang; Jordi Sardans; Josep Peñuelas; Fang-kun Yang (Environmental Pollution, 2025)

In situ aging mechanism of polyethylene microplastics during aerobic fermentation: Driven by fermentation conditions and plastic-degrading microorganisms - Qianting Zhuo; Wentao Gao; Zhuoyi Zhang; Ya Su; Ranran Wei; Lujia Han; Guangqun Huang (Chemical Engineering Journal, 2025)

Scalable coaxial wet-spinning of core-shell triboelectric fibers for self-powered smart fabrics - Zhihao Peng; Ying Chen; Xulong Zheng; Tianyu Wang; Fujun Han; Kairui Wang; Yiyan Gao; Ya Cheng; Guanghui Gao (Chemical Engineering Journal, 2025)

A polysaccharide smart packaging materials: Anthocyanin microcapsules synergized with nanosilver co-filled gellan gum/sodium alginate film for monitoring chilled mutton freshness - Zhaoyang Song; Wenjing Ni; Ya Zheng; Yabin Ma; Yinjuan Cao; Ling Han; Qunli Yu (Carbohydrate Polymers, 2025)

Nanocellulose-assisted construction of conductive gradient hydrogel for remote actuated and self-sensing soft actuator - Ya Lu; Shengnan Li; Yuanyuan Ma; Fang Deng; Yiying Yue; Shaohua Jiang; Mingqiang Ye; Yihui Zhou; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2025)

Effects of freeze–thaw cycles on the deformation and microstructure of silt - Yu-zhi Zhang; Ya-qian Dong; Jian-zhou Wang; Meng Wang; Yi-han Cui; Xiao-kang Kou (Cold Regions Science and Technology, 2025)

Fluoride Induces Spermatogonial Apoptosis via IP3R-MCU-Mediated Mitochondrial Calcium Overload - Rong Wang; Han Wang; Wenjing Gong; Xiaoqian Chen; Mengli Zheng; Ya Cui; Chunmei Liang; Jiayue Hu; Yuanhua Chen; Yanli Ji (Biological Trace Element Research, 2025)

The different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Biodegradable and non-biodegradable microplastics affect greenhouse gas emissions through chemical diversity and microbial biodiversity - Ying Guo; Yajuan Tang; Yi Xing; Chen Hong; Wei Su; Wei Wen; Haobo Ya; Jiayu Chen; Han Zhang; Duo Zhang; Wenxin Li; Yixiang Chen; et al. (Journal of Hazardous Materials, 2025)

Efficient degradation of dichloromethane by novel cell-immobilized-filled biotrickling filters: Performance and mechanisms - Yaxue He; Xiaoyan Li; Rui Han; Aohan Zhang; Ya Deng; Piet N.L. Lens; Christian Kennes; Zhao Huang; Jianmeng Chen; Guangfeng Yang; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Structural characterization, interaction mechanism and thermal stability of dual-fibrous complexes formed by rice glutelin fibrils and cellulose nanocrystals - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

Photo-induced aggregation of hole-transport material for enhancing photoelectrochemical performance in sensing ochratoxin - Han-Mei Deng; Ning Yang; Jie Xu; Xin-Ci Geng; Ya-Li Yuan; Ruo Yuan; Ya-Qin Chai (Chemical Engineering Journal, 2025)

Microbial-Modified Organosilica-Based Dual-Mode Fluorescent Probe for Zn²⁺ and pH Sensing with Potential Application in Gut Immunity Modulation - Qing-Qing Han; Fang Chen; Zhao-Lin Zhang; Dong-Ya Chen (Journal of Fluorescence, 2025)

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

Four new fluorenones isolated from the mycelia of medicinal mushroom Piptoporus soloniensis (Dubois:Fr.) Pilat and their anti-inflammatory activity - Lan Yao; Yi-Fan Sun; Ren-Ya Ji; Zi-Chen Tian; Shu-Han Zhang; Gen-Wei Zhang; Jian-Hua Lv (Natural Product Research, 2025)

Characterization of ColA as a virulence factor of Vibrio alginolyticus H1 pathogenic to cuttlefish Sepia pharaonis - Haijuan Dai; Weibo Shi; Ya Li; Ruibing Peng; Maowang Jiang; Xiamin Jiang; Weiwei Zhang; Huajun Zhang; Qingxi Han (Aquaculture, 2025)

Mapping the vertical city: AI-driven analysis of volumetric urban space use - Yi-Ya Hsu; Hoon Han (Sustainable Cities and Society, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Enclosed-terrain urbanized areas require vertically stratified air quality management: Insights from particulate matter vertical observations in China's Sichuan Basin - Xi Shu; Xue Qiao; Ya Tang; Philip K. Hopke; Qi Ying; Junfeng Wang; Bin Han; Zhongjun Xu; Zhonglin Xia; Yinhong Ma; Yuan Dai; Jun Leng (Journal of Environmental Management, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Coupled effects of amoxicillin and copper on high-risk antibiotic resistance gene dynamics during dairy manure aerobic composting - Ya Su; Ranran Wei; Qianting Zhuo; Chen Fang; Pingfan Wu; Lujia Han; Guangqun Huang (Chemical Engineering Journal, 2025)

Nanocellulose-mediated double-network conductive organohydrogels with self-adhesive, biocompatible and environmentally tolerant properties for wearable biosensors - Chunxiao Zheng; Jingren Ma; Ya Lu; Mingqiang Ye; Yihui Zhou; Weisheng Yang; Shuijian He; Shaohua Jiang; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2025)

Targeting mitochondrial dysfunction: an innovative strategy for treating renal fibrosis - Yi-Jin Wu; Yan-Rong Yang; Ya-Ling Yan; Han-Yinan Yang; Jun-Rong Du (Molecular and Cellular Biochemistry, 2025)

Development of dCAPS markers for sdhB mutants in fungicide-resistant Botrytis cinerea isolates - Rong Zeng; Ping Gao; Lihui Xu; Ya’nan Yuan; Yufei Han; Jiaxi Tian; Yuhong Wei; Shigang Gao; Zhiwei Song; Pu Zhu; Fuming Dai (Journal of Plant Pathology, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Membranal phosphatidylglycerol enhances oxygen diffusion and release from cyanobacteria - Jian-Lu Duan; Yi Han; Xiao-Yu Liu; Mei-Yan Liu; Yu-Chen Sun; Jing-Ya Ma; Xiao-Dong Sun; Yue Wang; Miao-Miao Tan; Bo Gong; Xian-Zheng Yuan (Water Research, 2025)

Assessment and projection of carbon density in China: An integrated approach combining Boruta-SHAP-machine learning and structural equation modeling - Ya Wen; Xue Han; Zizhao Ma; Ruirui Zhang (Remote Sensing Applications: Society and Environment, 2025)

A new fossil record of Adiantum (Pteridaceae) from Oligocene of Qaidam Basin, Northwest China and its palaeoenvironmental implications - Hong-Yu Chen; Tao Yang; Ya Li; Dieter Uhl; Lei Han; Jia-Hao Cai; Li Zhang; Yong-Dong Wang; De-Fei Yan (Palaeoworld, 2025)

Functional clothing, an overlooked source of persistent textile fibers in the global microplastic pollution - Ya Gao; Feng Ning; Hui Wang; Jie Han; Eric Lichtfouse (Environmental Chemistry Letters, 2025)

Combining rape biochar with hydroxyapatite: An approach to reduce Cd availability and uptake in maize while enhancing bacterial abundance in alkaline contaminated soil - Meili Sun; Yihao Wang; Hui Han; Ya Feng; Jinwei Yan; Aminu Darma; Jianjun Yang (Applied Soil Ecology, 2025)

Underrated risk of antibiotic resistance genes dissemination mediated by bioaerosols released from anaerobic biological wastewater treatment system - Na-Na Han; Xue-Ping Wang; Jing-Ao Jin; Wen-Hui Li; Wen-Ya Yang; Nian-Si Fan; Ren-Cun Jin (Water Research, 2025)

Multiscale spatio‐temporal variability of suspended sediment front in the Yangtze River Estuary and its ecological effects - Yunfei Du; Xiangju Han; Ya Ping Wang; Daidu Fan; Jicai Zhang (Water Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Two-step cascade degradation of Dongming lignite over Mo/N co-doped ZIF-67-based Co-Mo15@NC - Guang-Hui Liu; Hao-Dong An; Han Wang; Ya-Jun Ma; Yan-Jun Li; Yu-Hong Kang; Jie Kang; Wei Zhao; Sheng-Kang Wang; Xian-Yong Wei (Fuel, 2025)

Bioinspired hydrogel tactile sensor via pressure-intensified ion signals with self-healing and anti-frozen capability - Yi-Han Xue; Tian-Run Lv; Huiting Zhang; Ya-Qiong Yang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2025)

Identification and Validation of Biomarkers for Alzheimer’s Disease Based on Akt and Wnt Signaling Pathways in Mouse Models - Ya-Han Wang; Hong-Yun Wu; Chao Xin; Kai-Xin Zhang; Ji-Wei Zhang; Hong-Wei Zhi (Molecular Neurobiology, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Physiological and molecular insights into color variation and light intensity adaptation in Eucheuma perplexum with applications for selective cultivation - Ji-Long Liao; Zih-Ning Ding; Ya-Han Hsu; Jui-Sheng Chang (Algal Research, 2025)

Phenolic constituents from the branches of Viburnum chinshanense as potential α -amylase and α -glucosidase inhibitory agents - Hong-Juan Zhou; Meng-Ya Yang; Jia Chen; Wei Ji; Jian-Hua Shao; Zi-Han Wang; Chun-Chao Zhao (Natural Product Research, 2025)

Mapping of paddy field by Sentinel-1 SAR images and cadastre data in Yunlin, Taiwan - Jui-Han Yang; Kuo-Hsin Tseng; Shu-Ling Chen; Ya-Lun Tsai; Ray. Y. Chuang; Aive Liibusk; Chi-Farn Chen (International Journal of Remote Sensing, 2025)

Resilient urbanization assessment framework: A new perspective on urban resilience - Liudan Jiao; Zhirui Luo; Bowei Han; Liu Wu; Xiaosen Huo; Yu Zhang; Ya Wu (Urban Climate, 2025)

Undescribed alkaloids, peptides and polyketides from marine sediment-derived fungus Aspergillus terreus PPS1 - Yao-Yao Zheng; Guang-Shan Yao; Jiao-Jiao Li; Na Han; Jun-Qiu Mao; Ya-Hui Zhang; Ling Lv; Yang Liu; Chang-Yun Wang (Phytochemistry, 2025)

Newborn metabolomic signatures of maternal vanadium exposure and reduced birth size - Ya Xie; Gaga Mahai; Dejuan Zheng; Xinyu Zhang; Ling Yu; Hongxiu Liu; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Journal of Hazardous Materials, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Experimental Study on the Engineering Properties and Resistivity of Clay Contaminated by Alkali and Heavy Metal Ions - Yikun Chen; Ya Chu; Chao Yan; Wei Duan; Guojun Cai; Songyu Liu; Aimin Han (Water, Air, & Soil Pollution, 2025)

Ovule development and pollen tube growth in Tsuga chinensis: insights into the evolution of siphonogamy - Xin Shang; Ya-Xin Wang; Guo-Wei Jiang; Zhi-Han Chen; Xiao-Hang Bi; Jie Sun; Xin Zhang (Plant Cell Reports, 2025)

Deep learning for predicting water saturation using rock physics analysis and geostatistics theory: A case study of the Psh8 in GFZ area, Ordos Basin - Yong-gang Wang; Ya-ting Wang; De-yong Zhao; Ke-han Cai; Wei-fang Liu; Yu-ting He (Applied Geophysics, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Two E-clade protein phosphatase 2Cs enhance ABA signaling by dephosphorylating ABI1 in Arabidopsis - Ya Zhang; Liyuan Han; Junjie Liu; Miao Chang; Chuanling Li; Jian-Xiu Shang; Zhiping Deng; Wenqiang Tang; Yu Sun (Molecular Plant, 2025)

Chiral pesticide permethrin promotes the antibiotic resistance genes dissemination by transformation: Different chiral isomers engage in distinct regulatory pathways - Chenxi Li; Linjie Wang; Qi Dai; Yang Chong; Satoshi Utsunomiya; Honggui Wang; Ya Zhang; Jie Han (Journal of Hazardous Materials, 2025)

Machine learning-enhanced flavoromics: Identifying key aroma compounds and predicting sensory quality in sauce-flavor baijiu - Shuai Li; Yueran Han; Li Wang; Ya Zhang; Fan Wang; Youming Ou; Haoying Li; Liang Yang; Shuyi Qiu; Jun Lu (Food Chemistry, 2025)

Spice aldehydes improve emulsification stability of β-carotene by Schiff base reaction binding sodium caseinate as emulsion surface stabilizer - Ya Yu; Mengting Yuan; Ling Zhou; Yanan Liu; Ya Chen; Dongxu Wu; Zhihong Chen; Qingqing Yuan; Yang Han; Juhua Wang; Xiuheng Xue (Food Chemistry, 2025)

Effects of proteolysis pretreatment on the formation, structural changes and emulsifying properties of rice glutelin amyloid-like fibrils - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

Rational design of alginate lyase ALYI1 for improving the antioxidant activity of the alginate oligosaccharides - Jin-Ping Huang; Jin-Xin Zhao; Ming-jing Zhang; Jiru Han; Ya-Tong Han; Xue-Ting Wang; Tian-Bao Wu; Jun-Nan He; Cai-Mei Chen; Yan-Xia Zhou (Food Chemistry, 2025)

Preparation of sodium alginate/pectin/cellulose nanofibrils films containing black soybean seed coat anthocyanins for monitoring goat meat freshness - Siying Wang; Xinyue Han; Ya Chen; Yikai Shao; Jiaqing Song; Chunjie Yang; Shengqi Jiang; Rong Bai; Xiang Ye; Wu Ding (Food Control, 2025)

Biodetoxification of both AFB1 and ZEN by Bacillus subtilis ZJ-2019–1 in gastrointestinal environment and in mice - Jianwen Wu; Wei An; Zhenlong Wang; Boquan Gao; Jiaxue Wang; Ya Zhao; Bing Han; Hui Tao; Yaping Guo; Jinquan Wang; Xiumin Wang (Mycotoxin Research, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Antimicrobial p -terphenyl derivatives from the deep-sea cold seep-derived fungus Aspergillus candidus - Yi-Yi Liu; Jing-Ya Shi; Qi-Ran Liang; Guang-Ying Chen; Hai-Xin Chen; Zhuang Han; Xu-Hua Nong (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

A novel dual-responsive NIR fluorescent probe based on isophorone: Real-time detection of Al3 + in vivo and colorimetric sensing of pH through smartphone - Ya-Tong Liu; Yue Hou; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Meng-Xun Zhang; Hao Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2025)

Faceted-nanorods morphologies V2O5 nanostructures for enhanced CO2 photocatalytic conversion to CH4 under UV irradiation - Chih-Chiang Wang; An-Ya Lo; Yi-Jen Huang; Han-Chang Shih; Fuh-Shien Shieu; Tzu-Hsien Tseng; He-Ting Tsai (Journal of Environmental Chemical Engineering, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

A near-infrared multifunctional fluorescent bio-probe with large stokes shift and high quantum yield for effective determination of heavy metal lead and pesticide glyphosate in vitro and vivo - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Hua-Yong Zhao; Jing-Yi Li; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2025)

Unveiling the binding mechanism between wheat arabinoxylan and different molecular weights of wheat glutenins during the dough mixing process - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Jing-Yi Sun; Meng-Jia Fang; Wan-Hao Cai; Hui-Li Wang (Food Hydrocolloids, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

Research on a method for the evaluation of the pollution status of light petroleum hydrocarbon-contaminated sites via AHP-PSO - Han-liang Bian; Bo-wen Lv; Song-yu Liu; Ya Chu; Jianwei Zhang (Stochastic Environmental Research and Risk Assessment, 2025)

Vagus nerve stimulation (VNS) preventing postoperative cognitive dysfunction (POCD): two potential mechanisms in cognitive function - Zi-Feng Xie; Sheng-Yu Wang; Yuan Gao; Yi-Dan Zhang; Ya-Nan Han; Jin Huang; Mei-Na Gao; Chun-Guang Wang (Molecular and Cellular Biochemistry, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Tidal-driven N2O emission is a stronger resister than CH4 to offset annual carbon sequestration in mangrove ecosystems - Chunwei Fu; Zhibo Shen; Shiheng Tang; Fengying Li; Xin Quan; Yang Wang; Ya Zhuang; Jiasen Zhong; Jianan Liu; Jianzhong Su; Min Xu; Yu Han; et al. (Science of The Total Environment, 2025)

Delayed response of the coastal sedimentary record to the southward shift of the Huanghe (Yellow River) course during AD1128–1855 - Chengfeng Xue; Yang Yang; Xibin Han; Ya Ping Wang; Yining Chen; Xiaoming Xia; Jianjun Jia (Marine Geology, 2025)

Pickering emulsion gels with curdlan as both the emulsifier and the gelling agent: Emulsifying mechanism, gelling performance and gel properties - Liang Zhang; Xue Han; Ke-Jun Guo; Yi-Ping Ren; Ying Chen; Jie Yang; Jian-Ya Qian (Food Chemistry, 2025)

Two-ways regulation of the emulsion gel properties of curdlan by dry ball milling treatment and their relationships with the microstructures, emulsification characteristics and gel properties of ball milled curdlan - Xue Han; Ke-Jun Guo; Xiu-Nan Zhang; Ying Chen; Chun-Sen Wu; Liang Zhang; Jian-Ya Qian (Food Chemistry, 2025)

Exploring the binding mechanism and functional properties of lactoferrin-berberine complex: Based on multispectral analysis, molecular docking, and dynamics simulations - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

New insights into rice starch-gallic acid-whey protein isolate interactions: Effects of multiscale structural evolution and enzyme activity on starch digestibility - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Investigation of Feeding Effects and Environmental Impact of Fish-Feed Quality: Evidence from Crucian Carp Feeding Experiments - Jiayin Wang; Ran Wu; Jianhua Wang; Jiangtao Guo; Ya Zhang; Nanbing Shi; Jinxing Gu; Yibing Han; Xinyi Guo; Zhe Yu; Guoxi Li; Zhenjiang Yang (Fishes, 2025)
The effects of three types of feed, purchased from online stores and having similar prices, on the growth performance and culture environment of crucian carp (Carassius auratus) were studied in this experiment, which aimed to provide a reference for the evaluation and selection of fish feed. The results showed that feeding different feeds had a significant effect on crucian carp, and that the growth-promoting effect of HD feed (feed produced by Haida Company Limited) was significantly better than that of the other two feeds. For example, the weight gain rate (WGR) of fish in the HD group was 47.1% higher than that in the LD group (p

3D deformation analysis in a metropolitan area during ongoing subway construction using time series InSAR - Ajay Saraswat; Ya-Lun S. Tsai; Fang-Chiung Chen; Jen-Yu Han (Tunnelling and Underground Space Technology, 2025)

Soil erodibility and hillslope erosion processes affected by vegetation restoration duration - Ya Liu; Gang Liu; Ju Gu; Hongqiang Shi; Hairu Li; Yuqian Han; Dandan Liu; Xiaolin Xia; Zhen Guo (Soil and Tillage Research, 2025)

Gradient wood-derived hydrogel actuators constructed by an isotropic-anisotropic structure strategy with rapid thermal-response, high strength and programmable deformation - Ya Lu; Yuanyuan Ma; Fang Deng; Yiying Yue; Shaohua Jiang; Qinglin Wu; Huining Xiao; Jingquan Han (Chemical Engineering Journal, 2025)

Carboxymethyl cellulose organic gel polymer electrolyte enabling high performance of germanium-air batteries in a wide operating temperature range from −10 °C to 80 °C - Ya Han; Yingjian Yu (Chemical Engineering Journal, 2025)

Targeting Brain Endothelial Gasdermin D: A Shortcut to Remodel the Blood-Brain Barrier - Zhou-Yue Wu; Yi-Fan Luo; Ya-Ping Lu; Yi-Xuan Zhang; Feng Han (Neuroscience Bulletin, 2025)

Functionalized composite nanofiber membranes for selective steroid hormone micropollutants uptake from water: Role of cyclodextrin type - Alessandra Imbrogno; Han Ya Lin; Akhil Gopalakrishnan; Babak Minofar; Andrea I. Schäfer (Water Research, 2024)

Tri-functional molecular junction photocatalyst for cascade synthesis of N-benzylideneaniline derivatives - Xiao-Xin Li; Xiao-Xuan Hong; Zi-Yi Liao; Lei Zhang; Run-Han Li; Ying Zeng; Yue Liu; Shun-Li Li; Ya-Qian Lan (Science Bulletin, 2024)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Mechanisms of intermittent theta-burst stimulation attenuating nerve injury after ischemic reperfusion in rats through endoplasmic reticulum stress and ferroptosis - Xin-Ya Shen; Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Guo-Hui Xu; Xia Bi (Molecular Biology Reports, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS) exerts neuroprotective effects early in cerebral ischemia/reperfusion (I/R) injury. Intermittent theta-brust stimulation (iTBS), a more time-efficient modality of rTMS, improves the efficiency without at least decreasing the efficacy of the therapy. iTBS elevates cortical excitability, and in recent years it has become increasingly common to apply iTBS to patients in the early post-IS period. However, little is known about the neuroprotective mechanisms of iTBS. Endoplasmic reticulum stress (ERS), and ferroptosis have been shown to be involved in the development of I/R injury. We aimed to investigate the potential regulatory mechanisms by which iTBS attenuates neurological injury after I/R in rats. Methods Rats were randomly divided into three groups: sham-operated group, MCAO/R group, and MCAO/R + iTBS group, and were stimulated with iTBS 36 h after undergoing middle cerebral artery occlusion (MCAO) or sham-operated. The expression of ERS, ferroptosis, and apoptosis-related markers was subsequently detected by western blot assays. We also investigated the mechanism by which iTBS attenuates nerve injury after ischemic reperfusion in rats by using the modified Neurological Severity Score (mNSS) and the balance beam test to measure nerve function. Results iTBS performed early in I/R injury attenuated the levels of ERS, ferroptosis, and apoptosis, and improved neurological function, including mNSS and balance beam experiments. It is suggested that this mode of stimulation reduces the cost per treatment by several times without compromising the efficacy of the treatment and could be a practical and less costly intervention.

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Atmospheric Sulfur and Nitrogen Deposition in Five Nature Reserves of Sichuan Basin to Qinghai-Tibetan Plateau Transect Region, Southwestern China - Zhongjun Xu; Xi Shu; Han Yang; Liqiang Fu; Tingting Liu; Zhonglin Xia; Xue Qiao; Ya Tang (Chinese Geographical Science, 2024)

Optical fiber fluorescence Cu2+ sensing technology based on CdSe/ZnS quantum dots: Large detection range, low detection limit - Ya-nan Zhang; Wenchao Liang; Like Li; Hongrui Zhang; Shangwen Cao; Bo Han; Yong Zhao (Analytica Chimica Acta, 2024)

Evaluating sea ice influence on water exchange dynamics through three-dimensional hydrodynamic simulation in a semi-closed shallow sea - Na Zhang; Shuaiqi Liang; Keh-Han Wang; Qinghe Zhang; Ning Xu; Ya Ping Wang; Zhifa Wu; Tao Wang (Ocean & Coastal Management, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

Exploring the impact of sustainable finance on carbon emissions: Policy implications and interactions with low-carbon energy transition from China - Wei Zhang; Jie Han; Shiyi Kuang; Cem Işık; Ya Su; Gu Li Ni Ga Er Ju Lai Ti; Su Li; Zebang Xia; Anas Muhammad (Resources Policy, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Design of electronic conductive covalent-organic frameworks and their opportunities in lithium batteries - Yunyu Zhao; Ya Han; Yingjian Yu (Chemical Engineering Journal, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Chemical constituents from Elephantopus scaber L. and their chemotaxonomic significant - Ze-Ming Wu; Mei-Ya Lian; Xiao-Yu Han; Ming Bai; Shao-Jiang Song (Biochemical Systematics and Ecology, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

One new 12, 8-guaianolide sesquiterpene lactone with antihyperglycemic activity from the roots of Cichorium intybus - Xiu-hua Meng; Yin-an Pan; Han Lv; Xiao-qin Ding; De-quan Yin; Ya-nan Gai; Guan-ting Niu; Bing-ru Ren; Xiao-guo Qian; Jian Chen (Natural Product Research, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Chemosensory protein 22 in Riptortus pedestris is involved in the recognition of three soybean volatiles - Nan Gu; Yu-Wen Chen; Sai Ma; Qiang Liu; Jian-Qiao Li; Shu-Han Yang; Wen-Wen Zhu; Jin-Bu Li; Xiu-Yun Zhu; Xiao-Ming Li; Ya-Nan Zhang (Pesticide Biochemistry and Physiology, 2024)

Adsorption mechanism of sodium oleate at hematite/quartz–water interfaces: A quantitative molecular insight - Xinzhuang Fu; Ya Gao; Chuanxi Peng; Haisheng Han; Wei Sun; Tong Yue (Minerals Engineering, 2024)

Dual-recognition “turn-off-on” fluorescent Biosensor triphenylamine-based continuous detection of copper ion and glyphosate applicated in environment and living system - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Han-Wen Cui; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2024)

Heterostructure g-C3N4/Bi2MoO6 PVDF nanofiber composite membrane for the photodegradation of steroid hormone micropollutants - Zhi-Fu Lin; Han-Ya Lin; Ruey-An Doong; Andrea I. Schäfer (Journal of Hazardous Materials, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Prenylated dihydroflavones from the root barks of Morus alba - Jun-Yu Zhu; Han-Zhuang Weng; Di-Kai Tang; Jin-Chen Long; Zhuo-Ya Tang; Ye Chen; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Suppressing the Jahn–Teller effect in Mn-based Prussian blue analogues by linear (N O) anions - Qinghao Han; Zonghua Yang; Ya’nan Hu; Shuting Gao; Xingjun Liu; Cuiping Wang; Jiajia Han (Chemical Engineering Journal, 2024)

Evolutionary and functional analysis of metabotropic glutamate receptors in lampreys - Ruyu Zhuang; Zihao Yan; Yicheng Gao; Ayqeqan Nurmamat; Shuyuan Zhang; Min Xiu; Yuesi Zhou; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2024)

Co-occurrence of elevated arsenic and fluoride concentrations in Wuliangsu Lake: Implications for the genesis of poor-quality groundwater in the (paleo-)Huanghe (Yellow River) catchment, China - Ya-Ni Yan; Jun-Wen Zhang; Na Wu; Zi-Han Xia; Lin Liu; Zhi-Qi Zhao (Water Research, 2024)

Identification and functional analyses of CD4-1+ cells in grass carp (Ctenopharyngodon idella) - Xue-Qing Han; Yi-Ru Pan; Ya-Qin Zhong; Tian-Tian Tian; Xun Liu; Xu-Jie Zhang; Yong-An Zhang (Fish & Shellfish Immunology, 2024)

Nanocellulose-mediated bilayer hydrogel actuators with thermo-responsive, shape memory and self-sensing performances - Yuanyuan Ma; Ya Lu; Yiying Yue; Shuijian He; Shaohua Jiang; Changtong Mei; Xinwu Xu; Qinglin Wu; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Enhancing green sea turtle (Chelonia mydas) conservation for tourists at Little Liuqiu island, Taiwan: Application of deep learning algorithms - Vincent Y. Chen; Ya-Wen Wu; Chih-Wei Hu; Yu-San Han (Ocean & Coastal Management, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Type and evolution of the Middle Jurassic–Early Cretaceous basin at the northern margin of the Lhasa Block: constraints of sedimentary characteristics and provenance tracing based on zircon U-Pb ages - Fen-Qi Li; Shi-Zhen Zhang; Jun Li; Han Liu; Ya-Dong Qin (Palaeoworld, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

Ovalbumin amyloid-like fibrils/resveratrol self-assembling hydrogel: Preparation, characterization and formation mechanism - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Microecology of aerobic denitrification system construction driven by cyclic stress of sulfamethoxazole - Xiao-Yan Fan; Zhong-Xing Zhang; Xing Li; Yuan-Kun Liu; Shen-Bin Cao; Wen-Nian Geng; Ya-Bao Wang; Xiao-Han Zhang (Bioresource Technology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

The effects and mechanisms of deep straw incorporation and denitrifying bacterial agents on mitigating nitrate leaching and N2O emissions in four soil types in the North China Plain - Ya-Bo Zhang; Si-Yi Liu; Jun-Tao Wang; Hong J. Di; Li-Li Han; Pei-Pei Li; Ju-Pei Shen; Bing Han; Li-Mei Zhang (Agriculture, Ecosystems & Environment, 2024)

Redox mediator chlorophyll accelerates low-temperature biological denitrification with responses of extracellular polymers and changes in microbial community composition - Xiao-Yan Fan; Ya-Bao Wang; Xing-Li; Shen-Bin Cao; Xiao-Han Zhang; Wen-Nian Geng (Science of The Total Environment, 2024)

Effect of bovine hide gelatin antifreeze peptides on the quality of frozen dough treated with freeze-thaw cycles and its steamed bread - Chun-Chun Zhang; Ya-Ru Wang; Qin Yang; Han-Qing Chen (Journal of Cereal Science, 2024)

Smartphone-assisted carbon dots fluorescent sensing platform for visual detection of Thiophanate-methyl in fruits and vegetables - Ya Wang; Yanxin Ma; Hui Wang; Fei Shang; Bo Yang; Yong Han (Food Chemistry, 2024)

Pretreatment with low-frequency magnetic fields can improve the functional properties of pea globulin amyloid-like fibrils - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Chemistry, 2024)

Ultrasound-regulated fibrillation of arachin: Structural characteristics, foaming and emulsifying properties - Qin Yang; Ya-Ru Wang; Qing-Qing Liu; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Poly(vinylidene fluoride)-based composite membranes with continuous metal–organic framework layer for high-performance separators of lithium-ion batteries - Mengying Li; Sha Cheng; Jisong Zhang; Cheng Huang; Jiapei Gu; Jin Han; Xu Xu; Xiao Chen; Pengchao Zhang; Ya You (Chemical Engineering Journal, 2024)

Microbial mechanisms involved in negative effects of amoxicillin and copper on humification during composting of dairy cattle manure - Ya Su; Ling Zhou; Qianting Zhuo; Chen Fang; Jia You; Lujia Han; Guangqun Huang (Bioresource Technology, 2024)

Correction to: Efects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Effects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Responses of activated sludge to quorum sensing inhibitor and antibiotic compound stress: Interactions among abundant-rare genera, functional genes, and antibiotic resistance genes - Xiao-Yan Fan; Wen-Nian Geng; Xing Li; Yuan-Kun Liu; Shen-Bin Cao; Xiao-Han Zhang; Ya-Bao Wang (Journal of Environmental Chemical Engineering, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

Hsa-miR-877-5p Expression in Acute Ischemic Stroke Based on Bioinformatics Analysis and Clinical Validation - Si-Shuo Zhang; Ji-Wei Zhang; Kai-Xin Zhang; Wen-Qiang Cui; Hong-Wei Zhi; Hai-Tao Li; Hong-Yun Wu; Ya-Han Wang (Molecular Neurobiology, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Chemical constituents of Wikstroemia alternifolia and their neuroprotective activities - Qing-Ren Lu; Yan Wang; Zhuo-Ya Tang; Ye Chen; Han-Zhuang Weng; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

Scaling and cleaning of silica scales on reverse osmosis membrane: Effective removal and degradation mechanisms utilizing gallic acid - Shuqin Bai; Jue Han; Niqi Ao; Ru Ya; Wei Ding (Chemosphere, 2024)

Quantitative analysis of infectious precocity virus load and stunted growth syndrome via an immunohistochemical assay and reverse transcriptase quantitative real-time PCR in Macrobrachium rosenbergii - Yun-Ru Chiang; Ya-Yun Lu; Han-You Lin (Aquaculture, 2024)

Effects of dietary citric acid on growth performance, mineral status, body and muscle composition, muscle growth and mTOR signaling in yellow catfish Pelteobagrus fulvidraco fed with low-manganese diets - Tao Zhao; Jie-Jie Xu; Yannis P. Kotzamanis; Dian-Guang Zhang; Yi-Chuang Xu; Hua Zheng; Ya-Kang Han; Zhi Luo (Aquaculture, 2024)

Reclaimed seawater discharge – Desalination brine treatment and resource recovery system - Wei Han Tu; Ya Zhao; Wei Ping Chan; Grzegorz Lisak (Water Research, 2024)

Enhanced solubility, thermal stability and antioxidant activity of resveratrol by complexation with ovalbumin amyloid-like fibrils: Effect of pH - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Recycling of waste calcium carbonate in lignocellulosic biorefining chain for chiral lactic acid production - Bin Zhang; Qingmei Han; Qi Liu; Ya Wang; Jie Bao (Bioresource Technology, 2024)

Cadmium promotes the binding and centrosomal translocation of CCDC85C and PLK4 via ROS-GCLM pathway to trigger centrosome amplification in colon cancer cells - Ya Wen Han; Si Xian Xu; Jun Zhang; Yuan Fei Li; Peng Xu; Shao Chin Lee; Ji Zhong Zhao (Toxicology Letters, 2024)

Formation and structural characteristics of pea globulin amyloid-like fibrils pretreated with low-frequency magnetic field - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

A quantitative innovation perspective on synergism and selectivity mechanism of mixed collectors in flotation - Ya Gao; Xinzhuang Fu; Sultan Ahmed Khoso; Zujiang Pan; Haisheng Han; Wei Sun; Tong Yue (Minerals Engineering, 2024)

Effects of wild boar grubbing on the soil nematode community subject to seasonal variation in a broad-leaved Korean pine forest in Northeast China - Zhong Jie Sun; Heikki Setälä; Ya Xuan Cui; Chen Meng; Ming Ming Cui; Feirong Ren; Shi Jie Han; Jun Qiang Zheng (Forest Ecology and Management, 2024)

Combined influence of rotated transverse anisotropy in mechanical parameters and hydraulic conductivity of soils on reliability evaluation of an unsaturated slope under rainfalls - Lei-Lei Liu; Han Han; Shi-Ya Huang; Lei Huang; Yung-Ming Cheng (Computers and Geotechnics, 2024)

Sensitivity analysis of magnetic susceptibility under different climatic conditions during the late Pleistocene-Holocene period - Yuqian Han; Gang Liu; Chenxi Dan; Ya Liu; Qiong Zhang; Xiaolin Xia; Yang Zhang; Zhen Guo (CATENA, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

An in-fiber sensor for simultaneous measurement of cholesterol concentration and temperature based on SPR and MMI - Wanlu Zheng; Bo Han; Ya-nan Zhang; Lijun Liu; Yong Zhao (Analytica Chimica Acta, 2024)

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Maize straw application reduced cadmium and increased arsenic uptake in wheat and enhanced the rhizospheric bacterial communities in alkaline-contaminated soil - Aminu Darma; Ya Feng; Chao He; Hui Han; Peiman Zandi; Elke Bloem; Jianjun Yang (Journal of Environmental Management, 2023)

Analysis of matrix properties on ballistic mechanisms of aramid fabric composites: From experiment to numerical simulation - Feilong Han; Chenghao Wang; Ya Zhang; Ziyu Wang; Hangyu Yue; Lishuai Zong; Jinyan Wang; Xigao Jian (Chemical Engineering Journal, 2023)

The effects of AtEXO70E2 overexpression on the secretion and production of recombinant proteins in tobacco BY-2 suspension cells - Ya Li; Juan Han; Yugu Xu; Yun Wang; Guopeng Miao (In Vitro Cellular & Developmental Biology - Plant, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Identification of cadmium phytoavailability in response to cadmium transformation and changes in soil pH and electrical conductivity - Zhuoyi Yan; Wenchuan Ding; Gengxin Xie; Ming Yan; Jianbing Li; Ya Han; Xin Xiong; Chen Wang (Chemosphere, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Nitrogen evolution during membrane-covered aerobic composting: Interconversion between nitrogen forms and migration pathways - Jinpeng Xiong; Qianting Zhuo; Ya Su; Huiwen Qu; Xueqin He; Lujia Han; Guangqun Huang (Journal of Environmental Management, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Flexural properties of ultra-high performance fiber reinforced concrete based on three-dimensional random distribution of steel fibers - Ya Lu; Jingcheng Han; Puyan Wang; Xiangguo Wu; Hyeon-Jong Hwang; Jian Zhou; Ran Li; Sung-Hyun Kim; Ho-Jun Lee (Engineering Structures, 2023)

Customizing CoSe2/Ti3C2Tn MXene hybrid inks toward high-energy-density 3D-printed K-ion hybrid capacitors - Wenfeng Liu; Yuyang Yi; Zeyu He; Tao Han; Jingyu Sun; Ji Zhou; Ya-yun Li (Chemical Engineering Journal, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Ajpacifastin-like is involved in the immune response of Apostichopus japonicus challenged by Vibrio splendidus - Wenyang Ma; Ya Li; Weibo Shi; Weiwei Zhang; Qingxi Han (Fish & Shellfish Immunology, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Impact of host plants on biological characteristics and Vg/VgR expression of Spodoptera frugiperda - Shi-Peng Han; Ya-Yuan Zhou; Da Wang; Qiu-Ju Qin; Peng Song; Yun-Zhuan He (Journal of Pest Science, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Allelopathy of p-coumaric acid on Limnothrix sp., a bloom-forming cyanobacteria - Liping Wu; Lingzhi Li; Pan Dong; Liang Zhang; Hui Tang; Ya Han; Gengxin Xie (Algal Research, 2023)

Pallamins A–C, ent-labdane and pallavicinin based dimers from the Chinese liverwort Pallavicinia ambigua (mitt.) stephani - Yi Li; Xiao-Bin Li; Jin-Chuan Zhou; Ze-Jun Xu; Ming-Zhu Zhu; Yan Zong; Jiao-Zhen Zhang; Jing-Jing Han; Ya-Jie Tang; Hong-Xiang Lou (Phytochemistry, 2023)

Combined effects of amoxicillin and copper on nitrogen transformation and the microbial mechanisms during aerobic composting of cow manure - Ya Su; Jinpeng Xiong; Chen Fang; Huiwen Qu; Lujia Han; Xueqin He; Guangqun Huang (Journal of Hazardous Materials, 2023)

Predicting the interrill erosion rate on hillslopes incorporating soil aggregate stability on the Loess Plateau of China - Ya Liu; Gang Liu; Hai Xiao; Chenxi Dan; Chengbo Shu; Yuqian Han; Qiong Zhang; Zhen Guo; Yang Zhang (Journal of Hydrology, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Tumor microenvironment as a bioreactor for Au&Fe3O4-DNA complex synthesis and targeted cancer therapy - Yi Han Wang; Ke Huang; Zhao Jian Qin; Hong Jie Xiong; Teng Fei Liu; Ting Ya Wang; Xiang Dong Lai; Xiao Hui Liu; Hui Jiang; Xue Mei Wang (Chemical Engineering Journal, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Microbial community evolution and functional trade-offs of biofilm in odor treatment biofilters - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Guan-Yu Jiang; Meng-Fei Han; Ji-Guang Deng; Hsing-Cheng Hsi (Water Research, 2023)

Hexavalent chromium causes centrosome amplification by inhibiting the binding between TMOD2 and NPM2 - Meng Lu Zhao; Jia Xin Wang; Xue Kai Bian; Jun Zhang; Ya Wen Han; Si Xian Xu; Shao Chin Lee; Ji Zhong Zhao (Toxicology Letters, 2023)

Rapid screening of diarylpentanoids from Daphne bholua - Shu-Hui Dong; Mei-Ya Lian; Jin-Ling Han; Yun-Fei Ai; Xiao-Fang Zhou; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Trace ultrafine Ru nanoparticles on Ni/Al hydrotalcite-derived oxides supports as extremely active catalysts for N-ethylcarbazole hydrogenation - Bin Wang; Shi-yuan Wang; Shu-han Lu; Pei-ya Li; Tao Fang (Fuel, 2023)

Comparison of the assembly behavior and structural characteristics of arachin and conarachin amyloid-like fibrils - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Nitrate induced precise atom substitution and vacancies for overall water splitting - Ya-Nan Zhou; Yi-Wen Dong; Yang Wu; Bin Dong; Hai-Jun Liu; Xue-Jun Zhai; Guan-Qun Han; Da-Peng Liu; Yong-Ming Chai (Chemical Engineering Journal, 2023)

PAX5 aberrant expression incorporated in MIPI-SP risk scoring system exhibits additive value in mantle cell lymphoma - Xin Zhang; Yang Han; Yu Nie; Yujie Jiang; Xiaohui Sui; Xueling Ge; Fang Liu; Ya Zhang; Xin Wang (Journal of Molecular Medicine, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Effect of ferulic acid covalent conjugation on the functional properties and antigenicity of β-lactoglobulin - Yu-Ting Xue; Ya-Ning Han; Yan Wang; Ying-Hua Zhang; Yu-Qi Yin; Bo-Hao Liu; Han-Lin Zhang; Xin-Huai Zhao (Food Chemistry, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Effects of micro-positive pressure environment on nitrogen conservation and humification enhancement during functional membrane-covered aerobic composting - Jinpeng Xiong; Ya Su; Huiwen Qu; Lujia Han; Xueqin He; Jianbin Guo; Guangqun Huang (Science of The Total Environment, 2023)

Chitosan can improve the storage stability of ovalbumin fibrils at pH higher than isoelectric point - Ya-Ru Wang; Qin Yang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Effects of hydroxyapatite on safe wheat production and soil microbial functional genes in an alkaline soil contaminated with heavy metals - Ya Feng; Jianjun Yang; Darma Aminu; Hui Han; Yubo Yan; Yihao Wang; Jin Liu; Xudong Wang (Environmental Research, 2023)

Pre exposure to enriched environment alleviates brain injury after ischemia-reperfusion by inhibiting p38MAPK/STAT1 pathway - Xin-Ya Shen; Yu Han; Zhen-Kun Gao; Ping-Ping Han; Xia Bi (Molecular Biology Reports, 2023)
Background Stroke is one of the major diseases that endangers human health. It is widely reported that enriched environment (EE) can improve the neurological function in different brain injury models. Recently, relevant researches have indicated that MAPK pathway is closely related to the inflammatory response in nervous system related diseases. However, whether pre exposure to EE (EE pretreatment) has a preventive effect, and its mechanism are not clear. Therefore, this study aimed to determine the possible benefits and related mechanisms of EE in preventing brain injury after acute ischemia-reperfusion. Methods Adult Sprague Dawley rats were kept in enriched or standardized environments for 21 days. Then the middle cerebral artery of rats was occluded for one hour and 30 min, and then reperfusion was performed. Then their neurological deficit score was evaluated. Cerebral edema, along with ELISA and protein quantities of p38MAPK, JNK, ERK, IL-1β, TNF-α, and co-localization of Iba1 were assessed. Changes in neuroinflammation and apoptosis were also detected in the penumbra cortex. Results Our research showed that EE pretreatment significantly alleviated acute cerebral ischemia-reperfusion injury in rats. Including the reduction of brain edema and apoptosis, and the improvement of neurological scores. In addition, the protein level of p38MAPK was significantly down regulated in EE pretreatment group, and the downstream protein STAT1 had the same trend. In addition, immunofluorescence results showed that Iba1 in EE pretreatment group decreased, the ELISA results showed that the classical proinflammatory cytokines increased significantly, while anti-inflammatory cytokines in EE pretreatment group increased, and the same results were obtained by Western blot analysis. Conclusion On the whole, our research demonstrated that EE pretreatment can have a protective effect on the organism by inhibiting the p38 MAPK/STAT1 pathway. Thus, EE can be one of the most promising means of disease prevention. Secondly, p38MAPK/STAT1 pathway may be a latent target for the prevention of acute ischemic stroke.

Heat-induced arachin and basil seed gum composite gels improved by NaCl and microbial transglutaminase: Gelling properties and structure - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Analysis of ballistic performance and penetration damage mechanisms of aramid woven fabric reinforced polycarbonate composites with different matrix content - Feilong Han; Ya Zhang; Chenghao Wang; Ziyu Wang; Hangyu Yue; Lishuai Zong; Jinyan Wang; Xigao Jian (Chemical Engineering Journal, 2023)

Effects of functional membrane coverings on carbon and nitrogen evolution during aerobic composting: Insight into the succession of bacterial and fungal communities - Jinpeng Xiong; Ya Su; Xueqin He; Lujia Han; Guangqun Huang (Bioresource Technology, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Influences of subcellular Ca redistribution induced by γ irradiation on the fruit firmness of refrigerated blueberries - Chen Wang; Ye Tao; Yanqiu Han; Rui Zhang; Lifeng Li; Ya Gao (Postharvest Biology and Technology, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

Fractionation analysis and risk assessment of potential toxic elements in reservoir sediments in central China - Kai Zhang; Ya Han; Kuangjia Li; Ziwei Guo; Qian Wang; Xiangchao Cui; Fengxia Yang; Zhongshuai Zhang (Environmental Science and Pollution Research, 2022)

Fine intervals are required when using point intercept transects to assess coral reef status - Chao-Yang Kuo; Cheng-Han Tsai; Ya-Yi Huang; Wei Khang Heng; An-Tzi Hsiao; Hernyi Justin Hsieh; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The Point Intercept Transect (PIT) method has commonly been used in recent decades for estimating the status of coral reef benthic communities. It is a simple method that is efficiently performed underwater, as benthic components are recorded only as presence or absence at specific interval points along transects. Therefore, PIT is also popular in citizen science activities such as Reef Check programs. Longer intervals are commonly associated with longer transects, yet sampling interval length can significantly influence benthic coverage calculations. Despite this, the relative accuracy of longer or shorter intervals related to transect length has not been tested for PIT. In this study, we tested the optimum intervals of PIT for several commonly used transect lengths using the bootstrap method on empirical data collected on tropical coral reefs and non-reefal coral communities. Our results recommend fine intervals of 10 cm or shorter, depending on the length of the transect, to increase the accuracy of estimating benthic community status on coral reefs. Permanent transects should also be considered in long-term monitoring programs to improve data quality.

Development of 45 SNP markers in Triplophysa hsutschouensis based on RAD sequencing - Ya Liu; Jiansheng Lai; Zhongmeng Zhao; Hongyu Ke; Han Zhao; Yeyu Chen; Xiaoyun Wu; Qiang Li (Conservation Genetics Resources, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Prediction of Water Inflow into Tunnel Crossing Intersecting Faults Based on IDB Seepage Model - Jing Wu; Li Wu; Ya-ni Lu; Yan-hua Han; Jun-jie Jiang (Geotechnical and Geological Engineering, 2022)

Roseicella aquatilis sp. nov., isolated from freshwater lake - Dan-Dan Zhang; Ya-Nan Zhao; Rui-Han He; Yu-Qi Yan; Zong-Jun Du (Archives of Microbiology, 2022)

Isolation and characterization of 45 SNP markers in Triplophysa tenuis - Ya Liu; Yeyu Chen; Jiansheng Lai; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Xiaoyun Wu; Jian Zhou; Qiang Li (Conservation Genetics Resources, 2022)

Assessing the Resilience of the Marine Economy: A Case Study of Southern China’s Marine Economy Circle - Yue Hu; Han Qian Zhou; Xiao Mei Jin; Ya Fang Shen; Yong Zhe Yan (Frontiers in Marine Science, 2022)
As an important part of the national economy, the marine economy will be subject to various internal and external disturbances in the process of development. Different regions will show different resilience. Based on four dimensions of “resistance–recovery–reorientation–renewal,” this paper measures the marine economic resilience of the four provinces covered within the China’s Southern Marine Economy Circle from 2008 to 2018 by establishing an evaluation index system. The results show that 1) the overall resilience of economy in the Southern Marine Economy Circle showed a fluctuating upward trend from 2008 to 2018. Although there was a decline in 2011–2012 due to natural disasters, the value quickly resumed its increasing trend. 2) At present, there are obvious relative differences in the resilience of marine economy in each region of China’s Southern Marine Economy Circle, and the polarization phenomenon is serious. Among them, Guangdong belongs to the high-value region and Fujian is in the middle, while Hainan and Guangxi are temporarily in the low-value area.

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Correction to: Detailed clinical features and genotype–phenotype correlation in an OTOF-related hearing loss cohort in Japan - Yoh-ichiro Iwasa; Shin-ya Nishio; Hidekane Yoshimura; Akiko Sugaya; Yuko Kataoka; Yukihide Maeda; Yukihiko Kanda; Kyoko Nagai; Yasushi Naito; Hiroshi Yamazaki; Tetsuo Ikezono; Han Matsuda; et al. (Human Genetics, 2022)

Detailed clinical features and genotype–phenotype correlation in an OTOF-related hearing loss cohort in Japan - Yoh-ichiro Iwasa; Shin-ya Nishio; Hidekane Yoshimura; Akiko Sugaya; Yuko Kataoka; Yukihide Maeda; Yukihiko Kanda; Kyoko Nagai; Yasushi Naito; Hiroshi Yamazaki; Tetsuo Ikezono; Han Matsuda; et al. (Human Genetics, 2022)
Mutations in the OTOF gene are a common cause of hereditary hearing loss and the main cause of auditory neuropathy spectrum disorder (ANSD). Although it is reported that most of the patients with OTOF mutations have stable, congenital or prelingual onset severe-to-profound hearing loss, some patients show atypical clinical phenotypes, and the genotype–phenotype correlation in patients with OTOF mutations is not yet fully understood. In this study, we aimed to reveal detailed clinical characteristics of OTOF -related hearing loss patients and the genotype–phenotype correlation. Detailed clinical information was available for 64 patients in our database who were diagnosed with OTOF -related hearing loss. As reported previously, most of the patients (90.6%) showed a “typical” phenotype; prelingual and severe-to-profound hearing loss. Forty-seven patients (73.4%) underwent cochlear implantation surgery and showed successful outcomes; approximately 85–90% of the patients showed a hearing level of 20–39 dB with cochlear implant and a Categories of Auditory Performance (CAP) scale level 6 or better. Although truncating mutations and p.Arg1939Gln were clearly related to severe phenotype, almost half of the patients with one or more non-truncating mutations showed mild-to-moderate hearing loss. Notably, patients with p.His513Arg, p.Ile1573Thr and p.Glu1910Lys showed “true” auditory neuropathy-like clinical characteristics. In this study, we have clarified genotype–phenotype correlation and efficacy of cochlear implantation for OTOF -related hearing loss patients in the biggest cohort studied to date. We believe that the clinical characteristics and genotype–phenotype correlation found in this study will support preoperative counseling and appropriate intervention for OTOF -related hearing loss patients.

Analysis and Research on Blasting Network Delay of Deep-Buried Diversion Tunnel Crossing Fault Zone Based on EP-CEEMDAN-INHT - Jing Wu; Li Wu; Miao Sun; Ya-ni Lu; Yan-hua Han (Geotechnical and Geological Engineering, 2022)

Numerical simulation of water inrush in a tunnel crossing faults: impacts of fault width, damage zone width, and fault permeability - Jing Wu; Xintong Wang; Li Wu; Ya-ni Lu; Yan-hua Han (Arabian Journal of Geosciences, 2022)

MiR-3918 Inhibits Tumorigenesis of Glioma via Targeting EGFR to Regulate PI3K/AKT and ERK Pathways - Ya Han; Hengmin Wang (Journal of Molecular Neuroscience, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Nanofiltration Membrane Fouling and Control Caused by Residual Aluminum in Feed Water - Hui-Bo Yu; Xian-Qiu Zhang; Xue Han; Zhen-Zhen Yang; Ya-Wen Zhou; Wen Ding; Ming-Xia Du (Water, Air, & Soil Pollution, 2022)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Therapeutic Potential of Cytokines in Demyelinating Lesions After Stroke - Yi-Sha Guo; Mei Yuan; Yu Han; Xin-Ya Shen; Zhen-Kun Gao; Xia Bi (Journal of Molecular Neuroscience, 2021)

Assessing the Fishery Resource Status of China’s Coastal Waters Using Surplus Production Models - Qingqing Zhang; Qun Liu; Ya’nan Han (Journal of Ocean University of China, 2021)

Loop-mediated isothermal amplification and PCR combined assay to detect and distinguish latent Colletotrichum spp. infection on strawberry - Ya Liu; Ying Ji; Yongchao Han; Lili Song; Liqing Zhang; Zhiyuan Ning; Weizhong Yan; Qinghua Gao; Ke Duan (Journal of Plant Pathology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

The circular RNA circSlc7a11 promotes bone cancer pain pathogenesis in rats by modulating LLC-WRC 256 cell proliferation and apoptosis - Han-Wen Chen; Xiao-Xia Zhang; Zhu-Ding Peng; Zu-Min Xing; Yi-Wen Zhang; Ya-Lan Li (Molecular and Cellular Biochemistry, 2021)
Treatment of bone cancer pain (BCP) caused by bone metastasis in advanced cancers remains a challenge in clinical oncology, and the underlying mechanisms of BCP are poorly understood. This study aimed to investigate the pathogenic roles of circular RNAs (circRNAs) in regulating cancer cell proliferation and BCP development. Eight differentially expressed circRNAs in the rat spinal cord were validated by agarose gel electrophoresis and Sanger sequencing. Expression of circRNAs and mRNAs was detected by quantitative RT-PCR. MTS assay and flow cytometry were performed to analyze cell proliferation and apoptosis, respectively. Differentially expressed mRNA profiles were characterized by deep RNA sequencing, hierarchical clustering, and functional categorization. The interactions among circRNAs, microRNAs (miRNAs), and mRNAs were predicted using TargetScan. Additionally, western blot was performed to determine the protein levels of Pax8, Isg15, and Cxcl10. Multiple circRNAs were differentially expressed in the spinal cords of BCP model rats; of these, circSlc7a11 showed the greatest increase in expression. The overexpression of circSlc7a11 significantly promoted cell proliferation and repressed apoptosis of LLC-WRC 256 and UMR-106 cells, whereas circSlc7a11 silencing produced the opposite effects. Altered expression of circSlc7a11 also induced substantial changes in the mRNA expression profiles of LLC-WRC 256 cells; these changes were linked to multiple apoptotic processes and signaling pathways, such as the chemokine signaling pathway, and formed a complex circRNA/miRNA/mRNA network. Additionally, Pax8, Isg15, and Cxc110 protein level in LLC-WRC 256 cells was consistent with the mRNA results. The circRNA circSlc7a11 regulates rat BCP development by modulating LLC-WRC 256 cell proliferation and apoptosis through multiple-signaling mechanisms.

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Sodium alginate/collagen hydrogel loaded with human umbilical cord mesenchymal stem cells promotes wound healing and skin remodeling - Zhenkun Zhang; Zhe Li; Ya Li; Yingying Wang; Minghao Yao; Kun Zhang; Zhenyu Chen; Han Yue; Jijing Shi; Fangxia Guan; Shanshan Ma (Cell and Tissue Research, 2021)

ATP dynamic regeneration strategy for enhancing co-production of glutathione and S-adenosylmethionine in Escherichia coli - Ya Wei Chen; Yuan Liao; Wei Zhen Kong; Shu Han Wang (Biotechnology Letters, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Incidence of antibiotic resistance in Vibrio spp - Ke‐Yan Loo; Vengadesh Letchumanan; Jodi Woan‐Fei Law; Priyia Pusparajah; Bey‐Hing Goh; Nurul‐Syakima Ab Mutalib; Ya‐Wen He; Learn‐Han Lee (Reviews in Aquaculture, 2020)
Vibrio species is a common natural inhabitant of brackish and saltwater. Vibrio sp. includes not only emerging pathogens but also well‐known and emerged pathogens, such as V. cholerae , V. parahaemolyticus and V. vulnificus . Although it is often harmless, pathogenic strains which could cause serious food‐borne illnesses/outbreaks in both humans and animals have been identified. Vibrio infection is usually self‐limiting and requires no clinical treatment. However, antibiotics are still required to treat severe cases of Vibrio infection. Recent reports have highlighted a rise in the presence of antibiotic‐resistant Vibrio in the environment. This hampers the clinical treatment of Vibrio infection and has been linked to the imprudent use of antibiotics in various fields such as human medicine, agriculture and animal husbandry. As a result, it has greatly jeopardized food security, threatened public health and impugned the growth of economy. Food is a potential vehicle of antibiotic‐resistant Vibrio where the resistant genes are transmitted to humans via ingestion of contaminated food. Hence, the surveillance, monitoring and management of antibiotic patterns of Vibrio are important for clinical treatment. This review focuses on different trends and global patterns of antibiotic resistance of Vibrio .

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Inhibitory effects of curcumin on H2O2-induced cell damage and APP expression and processing in SH-SY5Y cells transfected with APP gene with Swedish mutation - Xi-Jun Song; He-Yan Zhou; Ya-Xuan Sun; Han-Chang Huang (Molecular Biology Reports, 2020)

RBM4 modulates the proliferation and expression of inflammatory factors via the alternative splicing of regulatory factors in HeLa cells - Wei-Yang Wang; Weili Quan; Fan Yang; Ya-Xun Wei; Jia-Jun Chen; Han Yu; Jie Xie; Yi Zhang; Zhan-Fei Li (Molecular Genetics and Genomics, 2020)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Estimating biological reference points for Largehead hairtail (Trichiurus lepturus) fishery in the Yellow Sea and Bohai Sea - Yupeng Ji; Qun Liu; Baochao Liao; Qingqing Zhang; Ya’nan Han (Acta Oceanologica Sinica, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Neuronal nitric oxide synthase activity mediates Lycium barbarum polysaccharides-enhanced sexual performance without stimulating noncontact erection in rats - Andy C. Huang; Jia-Min Wu; Ya-Han Chang; Navneet Kumar Dubey; Allen W. Chiu; Chien-Yu Yeh; Tung-Hu Tsai; Kuei-Ying Yeh (Psychopharmacology, 2019)

Multi-Functional Desaturases in Two Spodoptera Moths with ∆11 and ∆12 Desaturation Activities - Yi-Han Xia; Ya-Nan Zhang; Bao-Jian Ding; Hong-Lei Wang; Christer Löfstedt (Journal of Chemical Ecology, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

A Literature Review of Blood-Disseminated P. marneffei Infection and a Case Study of this Infection in an HIV-Negative Child with Comorbid Eosinophilia - Xiu-jing Han; Dan-hong Su; Jian-yun Yi; Ya-wei Zou; Yu-ling Shi (Mycopathologia, 2019)

LncRNA ZBTB40-IT1 modulated by osteoporosis GWAS risk SNPs suppresses osteogenesis - Bing Mei; Ya Wang; Weiyuan Ye; Han Huang; Qian Zhou; Yuanyuan Chen; Yajing Niu; Manling Zhang; Qingyang Huang (Human Genetics, 2019)

Macrophage-derived CCL18 promotes osteosarcoma proliferation and migration by upregulating the expression of UCA1 - Yang Su; Yan Zhou; Yuan-jue Sun; Ya-Ling Wang; Jun-yi Yin; Yu-jing Huang; Jian-jun Zhang; Ai-na He; Kun Han; Hui-zhen Zhang; Yang Yao; Xiao-Bin Lv; et al. (Journal of Molecular Medicine, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Novel antidepressant effects of Paeonol alleviate neuronal injury with concomitant alterations in BDNF, Rac1 and RhoA levels in chronic unpredictable mild stress rats - Xiu-Ling Zhu; Jing-Jing Chen; Fei Han; Chuan Pan; Ting-Ting Zhuang; Ya-Fei Cai; Ya-Ping Lu (Psychopharmacology, 2018)

Association of Interleukin-17F gene polymorphisms with susceptibility to severe enterovirus 71 infection in Chinese children - Fei Li; Peipei Liu; Ya Guo; Zhenliang Han; Yedan Liu; Yuanyuan Wang; Long Song; Jianguo Cheng; Zongbo Chen (Archives of Virology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Characterization of industrial odor sources in Binhai New Area of Tianjin, China - Bo Han; Ya-ting Liu; Jian-hui Wu; Yin-chang Feng (Environmental Science and Pollution Research, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Interaction between enterprises and consumers in a market of carbon-labeled products: a game theoretical analysis - Rui Zhao; Jiaojie Han; Shaozhuo Zhong; Ya Huang (Environmental Science and Pollution Research, 2018)

Administration of fentanyl via a slow intravenous fluid line compared with rapid bolus alleviates fentanyl-induced cough during general anesthesia induction - Min-qiang Liu; Feng-xian Li; Ya-kun Han; Jun-yong He; Hao-wen Shi; Li Liu; Ren-liang He (Journal of Zhejiang University-SCIENCE B, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

Retraction Note to: Nucleolin Promotes TGF-β Signaling Initiation via TGF-β Receptor I in Glioblastoma - Shunzeng Lv; Jie Zhang; Mingzhi Han; Weiping Wang; Ya Zhang; Dongxiao Zhuang; Ranran Shi; Ruixiang Bian; Chengjun Yao (Journal of Molecular Neuroscience, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

AKTs/PKBs: molecular characterization, tissue expression and transcriptional responses to insulin and/or wortmannin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

IRS1 and IRS2: molecular characterization, tissue expression and transcriptional regulation by insulin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Inoculation with endophytic Bacillus megaterium H3 increases Cd phytostabilization and alleviates Cd toxicity to hybrid pennisetum in Cd-contaminated aquatic environments - Ya Li; Hui Han; Lin Yan He; Qi Wang; Xia Fang Sheng (Environmental Science and Pollution Research, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Identification of FECH gene multiple variations in two Chinese patients with erythropoietic protoporphyria and a review - Zhang-biao Long; Yong-wei Wang; Chen Yang; Gang Liu; Ya-li Du; Guang-jun Nie; Yan-zhong Chang; Bing Han (Journal of Zhejiang University-SCIENCE B, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

A new triterpenoid compound from stems and leaves of American ginseng - Liu Han; Zhuo Li; Qian Zheng; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2016)

Clinicopathological and Prognostic Significance of CD133 in Glioma Patients: A Meta-Analysis - Mingzhi Han; Laixiu Guo; Ya Zhang; Bin Huang; Anjing Chen; Weiliang Chen; Xupeng Liu; Shicheng Sun; Kun Wang; Ao Liu; Xingang Li (Molecular Neurobiology, 2016)

Cardioprotective Effects of Total Flavonoids Extracted from Xinjiang Sprig Rosa rugosa against Acute Ischemia/Reperfusion-Induced Myocardial Injury in Isolated Rat Heart - Xuejiao Hou; Jichun Han; Changsheng Yuan; Huanhuan Ren; Ya Zhang; Tao Zhang; Lixia Xu; Qiusheng Zheng; Wen Chen (Cardiovascular Toxicology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

RETRACTED ARTICLE: Nucleolin Promotes TGF-β Signaling Initiation via TGF-β Receptor I in Glioblastoma - Shunzeng Lv; Jie Zhang; Mingzhi Han; Weiping Wang; Ya Zhang; Dongxiao Zhuang; Ranran Shi; Ruixiang Bian; Chengjun Yao (Journal of Molecular Neuroscience, 2015)

Serotonin drives the activation of pulmonary artery adventitial fibroblasts and TGF-β1/Smad3-mediated fibrotic responses through 5-HT2A receptors - Chunyan Chen; Xinyuan Han; Fenling Fan; Ya Liu; Tingzhong Wang; Juanjuan Wang; Peijing Hu; Aiqun Ma; Hongyan Tian (Molecular and Cellular Biochemistry, 2014)

Phytoremediation of heavy metal contaminated soil by Jatropha curcas - Fang-Chih Chang; Chun-Han Ko; Ming-Jer Tsai; Ya-Nang Wang; Chin-Yi Chung (Ecotoxicology, 2014)

Extraction of heavy metals from contaminated soil by Cinnamomum camphora - Jian-Ren Ho; Hwong-Wen Ma; Yi-Chung Wang; Chun-Han Ko; Fang-Chih Chang; Fong-Long Feng; Ya-Nang Wang (Ecotoxicology, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

Evaluation of cloud and precipitation parameterization using a single-column model: A TWP-ICE case study - So-Young Kim; Ji-Young Han; In-Jin Choi; Soo Ya Bae (Asia-Pacific Journal of Atmospheric Sciences, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Src contributes to IL6-induced vascular endothelial growth factor-C expression in lymphatic endothelial cells - Yu-Han Huang; Hung-Yu Yang; Ya-Fen Hsu; Pei-Ting Chiu; George Ou; Ming-Jen Hsu (Angiogenesis, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Analysis of promoters of microRNAs from a Glycine max degradome library - Yi-qiang Han; Zheng Hu; Dian-feng Zheng; Ya-mei Gao (Journal of Zhejiang University-SCIENCE B, 2014)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Loss of RUNX3 expression may contribute to poor prognosis in patients with chondrosarcoma - Zhe Jin; Ya-Xin Han; Xiao-Rui Han (Journal of Molecular Histology, 2013)

Bayesian prestack seismic inversion with a self-adaptive Huber-Markov random-field edge protection scheme - Yu-Kun Tian; Hui Zhou; Han-Ming Chen; Ya-Ming Zou; Shou-Jun Guan (Applied Geophysics, 2013)

Joint land-sea seismic survey and research on the deep structures of the Bohai Sea areas - Tianyao Hao; Qingyu You; Lihua Liu; Chuanchuan Lv; Ya Xu; Zhiwei Li; Chunlei Zhao; Yanpeng Zheng; Chenguang Liu; Guozhong Han (Acta Oceanologica Sinica, 2013)

Distinct Expression of Mas1-Related G-Protein-Coupled Receptor B4 in Dorsal Root and Trigeminal Ganglia—Implications for Altered Behaviors in Acid-Sensing Ion Channel 3-Deficient Mice - Ya-Han Huang; Chin-Yu Chang; Chih-Cheng Chen; Chih-Dong Yang; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2013)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Local Farmers’ Perceptions of Climate Change and Local Adaptive Strategies: A Case Study from the Middle Yarlung Zangbo River Valley, Tibet, China - Chunyan Li; Ya Tang; Han Luo; Baofeng Di; Liyun Zhang (Environmental Management, 2013)

Two endosymbiotic bacteria, Wolbachia and Arsenophonus, in the brown planthopper Nilaparvata lugens - Lv-Yu Qu; Yi-Han Lou; Hai-Wei Fan; Yu-Xuan Ye; Hai-Jian Huang; Meng-Qi Hu; Ya-Ni Zhu; Chuan-Xi Zhang (Symbiosis, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Purification and characterization of a new alginate lyase from a marine bacterium Vibrio sp. - Ya Wang; En-Wen Guo; Wen-Gong Yu; Feng Han (Biotechnology Letters, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Angiopoietin-1 preconditioning enhances survival and functional recovery of mesenchymal stem cell transplantation - Xian-bao Liu; Han Chen; Hui-qiang Chen; Mei-fei Zhu; Xin-yang Hu; Ya-ping Wang; Zhi Jiang; Yin-chuan Xu; Mei-xiang Xiang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Value of a new post-procedural intravascular ultrasound score in predicting target vessel revascularization after coronary drug-eluting stents implantation - Kai Xu; Ya-ling Han; Quan-min Jing; Shou-li Wang; Ying-yan Ma; Xiao-zeng Wang; Geng Wang; Zu-lu Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Partial Purification and Characterization of Fibrinolytic Enzymes from Yellow Mealworm - Ming Xing Huang; Yun Ye; Ya Xiong Chen; Ya Li Han (International Journal of Peptide Research and Therapeutics, 2012)

Cyclic fluid shear stress promotes osteoblastic cells proliferation through ERK5 signaling pathway - Peng Li; Yan-chao Ma; Xiao-yun Sheng; Hai-tao Dong; Hua Han; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

Diurnal variation in relative photosynthetic performance of marestail (Hippuris vulgaris Linn.) Across a water temperature gradient using PAM fluorometry in Jiuzhaigou National Nature Reserve, Sichuan Province, China - Linan Gao; Ya Tang; Carla Bossard; Yan Wang; Zhiguo Han (Journal of Mountain Science, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Methyl jasmonate- and salicylic acid-induced d-chiro-inositol production in suspension cultures of buckwheat (Fagopyrum esculentum) - Yao-hui Hu; Ya-tong Yu; Chun-hong Piao; Jun-mei Liu; Han-song Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Soybean oil content QTL mapping and integrating with meta-analysis method for mining genes - Zhao-ming Qi; Qiong Wu; Xue Han; Ya-nan Sun; Xiang-yu Du; Chun-yan Liu; Hong-wei Jiang; Guo-hua Hu; Qing-shan Chen (Euphytica, 2011)

c-Src in paraventricular nucleus modulates sympathetic activity and cardiac sympathetic afferent reflex in renovascular hypertensive rats - Ying Han; Ning Yuan; Shu-Juan Zhang; Juan Gao; Zhen Shi; Ye-Bo Zhou; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

A recombinant peroxisome proliferator response element-driven luciferase assay for evaluation of potential environmental obesogens - Ya-Fen Wang; How-Ran Chao; Chia-Hsin Wu; Chu-Han Tseng; Ya-Ting Kuo; Tsui-Chun Tsou (Biotechnology Letters, 2010)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

Angiotensin-(1–7) and angiotension II in the rostral ventrolateral medulla modulate the cardiac sympathetic afferent reflex and sympathetic activity in rats - Li-Min Zhou; Zhen Shi; Juan Gao; Ying Han; Ning Yuan; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Detoxification of Gramine by the Cereal Aphid Sitobion avenae - Qing-Nian Cai; Ying Han; Ya-Zhong Cao; Yuan Hu; Xin Zhao; Jian-Long Bi (Journal of Chemical Ecology, 2009)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

To the article “Tissue-specific changes in heme oxygenase activity and level of nonprotein Thiols in C57Bl/6 mice after whole-body γ-irradiation”, Vol. 140, No. 3, pp. 341–344 (2005) - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

Tissue-Specific Changes in Heme Oxygenase Activity and Level of Nonprotein Thiols in C57Bl/6 Mice after Whole-Body γ-Irradiation - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)

Genetic Diversity in Crucian Carp (Carassius auratus) - Jing Luo; Ya-Ping Zhang; Chun-Ling Zhu; Wu-Han Xiao; Shun-You Huang (Biochemical Genetics, 1999)

Vertical distribution of wild Yakushima macaques (Macaca fuscata yakui) in the western area of Yakushima Island, Japan: Preliminary report - Shinichi Yoshihiro; Masaru Ohtake; Hajime Matsubara; Koichiro Zamma; Goro Han'ya; Yasuaki Tanimura; Hiroyuki Kubota; Ritsuko Kubo; Tatsuhiro Arakane; Toru Hirata; Mari Furukawa; Aki Sato; et al. (Primates, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)